English intonation an introduction - Wells, John C. 1939- (Cambridge Univ. Press, 2006)
"Intonation - the rise and fall of pitch in our voices - plays a crucial role in how we express meaning. This accessible introduction shows students how to recognize and reproduce the intonation patterns of English, providing clear explanations of what they mean and how they are used. It looks in particular at three key functions of intonation - to express our attitude, to structure our messages to one another, and to focus attention on particular parts of what we are saying. An invaluable guide to how English intonation works, it is complete with extensive exercises, drills and practice material, encouraging students to produce and understand the intonation patterns for themselves. The accompanying CD contains a wealth of spoken examples, clearly demonstrating English intonation in context. Drawing on the perspectives of both language teaching and linguistics, this textbook will be welcomed by both learners of English, and beginning undergraduates in phonetics and linguistics." http://www.loc.gov/catdir/enhancements/fy0619/2006299992-d.html.
Keywords: Englisch; English language -- Textbooks for foreign speakers; English language -- Intonation; English language -- Intonation -- Problems, exercises, etc; Intonation -- Linguistik; Lehrbuch